(untitled) (Journal of Oriental Studies, 2023)
Armenia’s historical connection with the Islamic world, having been part of its empires for an extended period, significantly influences the teaching methodology of the course "Introduction to Islamic Studies." This article explores how the thirteen-century history of coexistence with the Islamic world shapes the teaching approach for "Introduction to Islamic Studies" in the Armenian classroom, particularly emphasising incorporating the works of Armenian medieval historians into the curriculum. By adopting this approach, the course bridges the gap between Islamic and Armenian history, providing students with a strong sense of identity and relevance. Incorporating Armenian bibliographic sources into the curriculum enriches the course material and encourages students to engage in a deeper analysis of evidence, facts, and arguments. This practice cultivates critical thinking skills and empowers students to draw well-informed conclusions about historical events and figures.